INKONSISTENSI PUTUSAN MAHKAMAH AGUNG DALAM MEMBATALKAN PUTUSAN ARBITRASE - Widowaty, Yeni; Fitriyanti, Fadia (Jurnal Media Hukum, 2016)
This research has 3 aims, the first is to examines the consideration of the Supreme Court in deciding the cancellation of arbitration decision under Article 70 and beyond Article 70 of Arbitration Act, the second is to review and analyze theories used in the consideration of the Supreme Court to cancel the Arbitration Decision. The third is to formulate concept in deciding the cancellation of Arbitration based on the principle of justice. This type of research is normative judicial research. Approach used in this research is case study approach. In more detail of the data obtained, processed and analyzed and presented in descriptive qualitative. The result of the research is divided into several parts, the first shows that according to the consideration of Deision of Supreme Court No.729/K/Pdt.Sus/2008 see Article 70 of the Arbitrase Act is limitative, different with Supreme Court Decision No.03/Arb/BTU of 2005 interpeting Article is enunciatif. The second, the Great Judge who cancel the arbitrase decision according to Article 70 Arbitration Act which is limitative by using Analytical theory. the Great Judge cancel the arbitrase decision refers to reasons beyond Article 70 of Rbitrase Act using Progressive Law theory. The third, according to procedural fairness the reason for cancellation is based on decision Article No.70 Arbitrase Act is too limitative comparing to Article 34 of the UNICITRAL Model Law. This substantive justice should be limited to the signs, so that arbitrators use it arbitrarily.